PRNP variants in goats reduce sensitivity of detection of PrPSc by immunoassay. (May 2015) - Madsen-Bouterse, Sally A.; Schneider, David A.; Dassanayake, Rohana P.; Truscott, Thomas C.; Zhuang, Dongyue; Kumpula-McWhirter, Nancy; O'Rourke, Katherine I.
Diagnostic analyses often employ single antibody systems but are potentially limited by epitope sequence variation. United States regulatory testing for scrapie primarily uses antibody F99/97.6.1 for immunohistochemistry (IHC) of the prion protein associated with scrapie (PrP Sc ). Whereas the epitope bound by F99/97.6.1 is highly conserved in sheep, a polymorphism in caprine PRNP results in a glutamine to lysine change at codon 222 and affects PrP detection. This study evaluated the performance of immunoassays (Western blot and IHC) in the presence of PRNP polymorphisms observed in U.S. goat populations. Effects of naturally occurring caprine prion protein alterations at codons 142, 143, 146, 154, or 222 were first evaluated using bacterially expressed recombinant normal cellular prion protein (rec-PrP C ) and commercially available antibodies (F99/97.6.1, F89/160.1.5, L42, and SAF84). Detection of rec-PrP C using F89/160.1.5 was reduced by alterations at 142 and 143; this was also observed in brain PrP C from goats expressing these PRNP variants. Effect of allelic variation at 222 was confirmed by Western blot with F99/97.6.1. No differences were observed with L42 or SAF84. IHC of brain demonstrated reduced signal with F89/160.1.5 in animals heterozygous at 143. Decreasing F89/160.1.5 titers were used to demonstrate the impact of PrP Sc immunolabeling in preclinical goats and as a surrogate for F99/97.6.1 detection in 222 variants. In the absence of epitope-relevant knowledge of individual goat PRNP, a multi-antibody approach or an antibody that binds an invariant site may provide a more robust immunoassay of PrP Sc in classical scrapie, thus reducing the likelihood of false-negative results due to allelic variation.